Islam and Christianity on the periphery of the Golden Horde in the Middle Don region - Tsybin M.V. (Золотоордынское обозрение)
The purpose of the study is to analyze the data from the study of archaeological sites on the periphery of the Golden Horde in the Middle Don region, along with evidence from written sources about the spread of Islam and Christianity among the population of this area. Research materials: The paper examines the materials of Russian settlements, monuments of the Golden Horde circle (Novokharkovsky and Tagansky burial grounds), mausoleums near Krasnyi Village, and nomadic burials in the barrows. Written sources are involved (“Pimenov’s journey to Tsargrad,” the charters of Metropolitans Theognost and Alexei to the population of the Chervleny Yar). Results and scientific uniqueness: Archaeological materials allow us to talk about the coexistence of different confessional groups in the population on the periphery of the Golden Horde in the Middle Don region. The spread of Christianity in this area is associated with the Russian population. The information of the charters of Metropolitans Theognost and Alexei about the Christian population in the Prikhoper region is confirmed by the data of archaeological research. Among the population who left the Novokharkovsky burial ground, one can assume the spread of both Islam and Christianity. The influence of the traditions of Islam can be traced in the funeral rites of the Tagansky burial ground. The most striking evidence of the spread of Islam on the periphery of the Golden Horde in the Middle Don region is the mausoleums near Krasnyi Village. In the tombs studied in and around mausoleums, there are also remnants of paganism. Only a few nomadic burials in the barrows can be considered Muslim burials.